The Evolution of an Elective in Health Disparities and Advocacy: Description of Instructional Strategies and Program Evaluation - Gonzalez, Cristina M. (Acad Med, 2015)
PROBLEM: Health disparities remain pervasive in the United States. Training future physicians to address health disparities requires attention to both systemic and provider causes of disparities, but comprehensive curricula are lacking. APPROACH: Albert Einstein College of Medicine in Bronx, New York, offers a 13-session health disparities elective to first-year medical students. The curriculum covers three main content areas: background, provider contributions to health disparities, and systemic contributions to health disparities (i.e., social determinants of health). Teaching methods included didactic and multimedia presentations, reflective discussions, and skill-building seminars (e.g., addressing subconscious assumptions and advocacy training). The authors evaluated the course in 2010–2013 by comparing students’ summary scores for knowledge, attitudes, and self-reported confidence on pre- and postintervention tests. They investigated associations between students’ sociodemographic characteristics and changes in summary scores. OUTCOMES: Scores increased significantly in each domain: Mean knowledge scores increased from 63.6 (± 10.0), out of 100, to 76.4 (± 12.8); mean attitudes scores increased from 16.7 (± 1.9), out of 20, to 18.2 (± 1.1); mean confidence scores increased from 10.7 (± 1.5), out of 16, to 14.4 (± 1.7). Younger students (< 24) had greater changes in confidence than older students. Other sociodemographic characteristics were not associated with changes in any domain. NEXT STEPS: Exposure to health disparities instruction is important for medical students. The authors’ experience provides insights for incorporating such material into the compulsory curriculum. Future evaluation of outcomes from similar curricula should include measures of clinical behaviors (e.g., through clinical examinations).